(untitled) - Lytle, Charles F. (Boston, 2000)
General Zoology Laboratory Manual is ideal for the laboratory that emphasizes the dissection and microscopic study of live and preserved specimens. Recognized for its accuracy and readability, this manual is comprehensive in its representation of the major groups of animal phyla.This new edition is suitable for a wide range of course needs and structures.
Keywords: Zoology